Review of antioxidant-rich natural dietary products as protective and therapeutic factors against cadmium toxicity in living organisms - Quddus, Abdul; Yimer, Nurhusien; Abdul Basit, Muhammad; Khan, Saadiya; Amir, Maria (Universiti Putra Malaysia Press, 2021)
Advances in civilization processes and industrialization have doubled the release of toxic heavy metals into the environment, consequently elevating their presence in the food chains. Cadmium (Cd) is one of the severe toxic metals widely present in the atmosphere. The major route of animal or human exposure to Cd is through water or food ingestion and inhalation of particles or inhalation of fumes during various industrial processes. Continuous exposure to low levels of Cd results in a gradual deposition in different tissues of the body, causing toxic effects on the liver, kidneys, testes, and other vital organs. The beneficial effect of natural antioxidants against chemical induced toxicity is receiving more attention. Antioxidant-rich dietary products and their function in tempering free radicals produced in the body under different pathological conditions is an active research field. In the current review, we attempted to highlight the current research progress in the field of using antioxidant-rich natural dietary products and their function in mitigating or preventing health issues and tissue damage associated with Cd induced toxicity along with its mechanism.